Combating oppression with new commemorations
1 online resource (304 pages)
Keywords: Combating Oppression with New Commemorations examines the ways in which marginalized groups can confront oppressive regimes through commemorations and advocacy of their own heritage.Presenting case studies from across the globe, the volume provides invaluable insights into the diverse strategies and various disciplinary approaches being used to counter oppression through commemorations of the heritage of marginalized groups. Reminding the reader that such commemorations are often created by individuals who have directly confronted traumas of oppression, contributors emphasize that their survivance, successes, and vitality are tributes to human resilience and creativity. Chapters also demonstrate how such commemorations can advance recognition of the group's diverse legacies and cultural identity and help enhance social and economic equities for that population across local, regional, and national scales. It is also made clear that they can provide resources for reconciliation negotiations with other social collectives who seek to oppress the marginalized group. These dynamics can facilitate truth-telling, accountability, recovery of unrecorded histories, revitalization, increments of healing, and efforts to avoid future repetitions of past and present social traumas.Combating Oppression with New Commemorations will be essential reading for academics, and students working in heritage studies, archaeology, anthropology, material culture studies, landscape analysis, and museum studies. It will also be of great interest to practitioners and activists around the world.